Current Views and Principles of Therapy of Diabetic Neuropathy in Children and Adolescents (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Diabetic neuropathy- representing a complex of clinical and subclinical syndromes characterized by lesions of peripheral and/or autonomous nerve fibers, is the most frequent complication. The most common forms of diabetic neuropathy include chronic sensorimotor (distal) polyneuropathy, which accounts for more than half of all cases of specific complications of type 1 diabetes mellitus in children and adolescents with variability in the range of 4-30%.Data on the frequency of diabetic autonomic neuropathy in children are few and also contradictory; A. Verrotti et al., analyzing data from epidemiological studies, cite figures ranging from 25 to 75% for different clinical forms. The ambiguity of such contradictory data on the prevalence of this complication depends on the cohort of examined patients and is also a consequence of different approaches to diagnosis and interpretation of the results of instrumental methods of investigation.